Double Carbonylation Using Glyoxal (HCOCOH): A Practical Copper-Promoted Synthesis of Isatins from Primary and Secondary Anilines - Hui, Suzie Chin Kuan; Wei, Sun; Lu, Wang; Chungu, Xia; Meng, Guan Tay; Chao, Liu (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2017)
A novel double carbonylation process has been demonstrated with easily available HCOCOH (glyoxal) as the double carbonylation reagent. Simple CuCl2·2H2O (copper(II) chloride dihydrate) was used as the oxidant for this transformation. Under optimized reaction conditions, various primary and secondary anilines were double-carbonylated to afford their corresponding isatins (26 examples, up to 80% yields).